Analysis of Human Resource Management Strategies In Improving Organizational Performance In The Digital Era - Natasya Ainul Hikmah; Jeziano Rizkita Boyas; Ikhwan Abdilah (Universitas Nahdlatul Ulama Sidoarjo, 2025)
This study aims to analyze human resource management strategies in improving organizational performance in the digital era. The use of technology, such as HRIS (Human Resource Information System) and digital training platforms, has been shown to positively impact operational efficiency and employee skill development. HRIS enables companies to monitor employee performance more efficiently, while e-learning provides flexibility in skill development. The findings indicate that the implementation of technology in HR management accelerates recruitment, selection, and training processes, contributing to the overall improvement of organizational performance. Digitalization in HR management also offers companies the opportunity to create a continuous learning culture and become more adaptive to changes.